An Energy‐Efficient, Wood‐Derived Structural Material Enabled by Pore Structure Engineering towards Building Efficiency. Issue 1 (11th December 2019) - He, Shuaiming; Chen, Chaoji; Li, Tian; Song, Jianwei; Zhao, Xinpeng; Kuang, Yudi; Liu, Yang; Pei, Yong; Hitz, Emily; Kong, Weiqing; Gan, Wentao; Yang, Bao; et al.
Abstract: The development of high‐performance structural materials for high‐rise building applications is critical in achieving the energy conservation goal mandated by the Department of Energy (DOE). However, there is usually a trade‐off between the mechanical strength and thermal insulation properties for these materials. Here, the optimization is demonstrated of natural wood to simultaneously improve the mechanical properties and thermal insulation for energy efficient high‐rise wood buildings. The improved wood material (strong white wood) features a complete delignification followed by a partial densification process (pore structure control), which enables substantially enhanced mechanical properties (≈3.4× in tensile strength, ≈3.2× in toughness) and reduced thermal conductivity (≈44% decrease in the transverse direction). The complete delignification process removes all lignin and partial hemicellulose from the cell walls of the wood structure, leading to an all‐cellulose microstructure with numerous aligned cellulose nanofibers. The partial densification optimizes the porosity of the delignified cellulose scaffold while enhancing the effectiveness of hydrogen bonding among aligned cellulose nanofibers. The simultaneously improved mechanical and thermal insulation properties of the wood material render it highly desirable for a wide range of modern engineering applications, especially as an energy‐efficient, strong, lightweight, environmentally‐benign, scalable, and low‐cost building material. Abstract : An energy‐efficient, wood‐derived structural material with a high tensile strength of ≈161 MPa and a low transverse thermal conductivity of 0.09 W (m K) −1 is developed by a pore structure engineering strategy. The excellent mechanical and thermal insulation properties position it as a green and sustainable structural material for a wide range of engineering applications, especially for energy‐efficient buildings.